Regulation of integrin and growth factor signaling in biomaterials for osteodifferentiation - Wei, Qiang; Pohl, Theresa L. M.; Seckinger, Anja; Spatz, Joachim P.; Cavalcanti-Adam, Elisabetta A. (Beilstein Journal of Organic Chemistry, 2015)
Stem cells respond to the microenvironment (niche) they are located in. Under natural conditions, the extracellular matrix (ECM) is the essential component the in stem cell niche, in which both integrin ligands and growth factors are important regulators to directly or indirectly modulate the cell behavior. In this review, we summarize the current knowledge about the potential of integrin ligands and growth factors to induce osteogenic differentiation of stem cells, and discuss the signaling pathways that are initiated by both individual and cooperative parameters. The joint effect of integrin ligands and growth factors is highlighted as the multivalent interactions for bone therapy.
Keywords: biomaterials; growth factor; integrin; osteodifferentiation; stem cells

(untitled) - De Long, W. G., Jr; Einhorn, T. A.; Koval, K.; McKee, M.; Smith, W.; Sanders, R.; Watson, T. (J. Bone Joint Surg. Am., 2007)

(untitled) - Kimelman, N.; Pelled, G.; Helm, G. A.; Huard, J.; Schwarz, E. M.; Gazit, D. (Tissue Eng., 2007)

(untitled) - Nombela-Arrieta, C.; Ritz, J.; Silberstein, L. E. (Nat. Rev. Mol. Cell Biol., 2011)

(untitled) - Marie, P. J. (Nat. Rev. Endocrinol., 2013)

(untitled) - Hynes, R. O. (Cell, 2002)

(untitled) - Jalali, S.; del Pozo, M. A.; Chen, K.-D.; Miao, H.; Li, Y.-S.; Schwartz, M. A.; Shyy, J. Y.-J.; Chien, S. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Dalby, M. J.; Gadegaard, N.; Oreffo, R. O. C. (Nat. Mater., 2014)

(untitled) - Lienemann, P. S.; Lutolf, M. P.; Ehrbar, M. (Adv. Drug Delivery Rev., 2012)

(untitled) - King, W. J.; Krebsbach, P. H. (Adv. Drug Delivery Rev., 2012)

(untitled) - Bishop, J. R.; Schuksz, M.; Esko, J. D. (Nature, 2007)

(untitled) - Hynes, R. O. (Science, 2009)

(untitled) - Wozney, J. M.; Rosen, V.; Celeste, A. J.; Mitsock, L. M.; Whitters, M. J.; Kriz, R. W.; Hewick, R. M.; Wang, E. A. (Science, 1988)

(untitled) - Ripamonti, U.; Ferretti, C.; Teare, J.; Blann, L. (J. Craniofac. Surg., 2009)

(untitled) - Park, M. S.; Kim, S.-S.; Cho, S.-W.; Choi, C. Y.; Kim, B.-S. (J. Biomed. Mater. Res., Part B, 2006)

(untitled) - Street, J.; Bao, M.; deGuzman, L.; Bunting, S.; Peale, F. V., Jr; Ferrara, N.; Steinmetz, H.; Hoeffel, J.; Cleland, J. L.; Daugherty, A.; van Bruggen, N.; Redmond, H. P.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Brizzi, M. F.; Tarone, G.; Defilippi, P. (Curr. Opin. Cell Biol., 2012)

(untitled) - Streuli, C. H.; Akhtar, N. (Biochem. J., 2009)

(untitled) - Humphries, J. D.; Byron, A.; Humphries, M. J. (J. Cell Sci., 2006)

(untitled) - Winograd-Katz, S. E.; Fässler, R.; Geiger, B.; Legate, K. R. (Nat. Rev. Mol. Cell Biol., 2014)

(untitled) - Plow, E. F.; Haas, T. K.; Zhang, L.; Loftus, J.; Smith, J. W. (J. Biol. Chem., 2000)

(untitled) - Schwab, E. H.; Halbig, M.; Glenske, K.; Wagner, A.-S.; Wenisch, S.; Cavalcanti-Adam, E. A. (Int. J. Med. Sci., 2013)

(untitled) - Rechenmacher, F.; Neubauer, S.; Polleux, J.; Mas-Moruno, C.; De Simone, M.; Cavalcanti-Adam, E. A.; Spatz, J. P.; Fassler, R.; Kessler, H. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kilian, K. A.; Mrksich, M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Watt, F. M.; Huck, W. T. S. (Nat. Rev. Mol. Cell Biol., 2013)

(untitled) - Connelly, J. T.; Gautrot, J. E.; Trappmann, B.; Tan, D. W.-M.; Donati, G.; Huck, W. T. S.; Watt, F. M. (Nat. Cell Biol., 2010)

(untitled) - McBeath, R.; Pirone, D. M.; Nelson, C. M.; Bhadriraju, K.; Chen, C. S. (Dev. Cell, 2004)

(untitled) - Arnold, M.; Cavalcanti-Adam, E. A.; Glass, R.; Blümmel, J.; Eck, W.; Kantlehner, M.; Kessler, H.; Spatz, J. P. (ChemPhysChem, 2004)

(untitled) - Cavalcanti-Adam, E. A.; Aydin, D.; Hirschfeld-Warneken, V. C.; Spatz, J. P. (HFSP J., 2008)

(untitled) - Huang, J.; Gräter, S. V.; Corbellinl, F.; Rinck, S.; Bock, E.; Kemkemer, R.; Kessler, H.; Ding, J.; Spatz, J. P. (Nano Lett., 2009)

(untitled) - Das, R. K.; Zouani, O. F.; Labrugère, C.; Oda, R.; Durrieu, M.-C. (ACS Nano, 2013)

(untitled) - Dalby, M. J.; Gadegaard, N.; Tare, R.; Andar, A.; Riehle, M. O.; Herzyk, P.; Wilkinson, C. D. W.; Oreffo, R. O. C. (Nat. Mater., 2007)

(untitled) - Tsimbouri, P. M.; McMurray, R. J.; Burgess, K. V.; Alakpa, E. V.; Reynolds, P. M.; Murawski, K.; Kingham, E.; Oreffo, R. O. C.; Gadegaard, N.; Dalby, M. J. (ACS Nano, 2012)

(untitled) - Liu, Y.; Medda, R.; Liu, Z.; Galior, K.; Yehl, K.; Spatz, J. P.; Cavalcanti-Adam, E. A.; Salaita, K. (Nano Lett., 2014)

(untitled) - Downing, T. L.; Soto, J.; Morez, C.; Houssin, T.; Fritz, A.; Yuan, F. L.; Chu, J.; Patel, S.; Schaffer, D. V.; Li, S. (Nat. Mater., 2013)

(untitled) - Giancotti, F. G.; Tarone, G. (Annu. Rev. Cell Dev. Biol., 2003)

(untitled) - Clark, E. A.; Brugge, J. S. (Science, 1995)

(untitled) - Schlaepfer, D. D.; Hunter, T. (Trends Cell Biol., 1998)

(untitled) - Cox, E. A.; Bennin, D.; Doan, A. T.; O'Toole, T.; Huttenlocher, A. (Mol. Biol. Cell, 2003)

(untitled) - Lim, S.-T. (Mol. Cells, 2013)

(untitled) - Lim, S.-T.; Miller, N. L. G.; Nam, J.-O.; Chen, X. L.; Lim, Y.; Schlaepfer, D. D. (J. Biol. Chem., 2010)

(untitled) - Trappmann, B.; Gautrot, J. E.; Connelly, J. T.; Strange, D. G. T.; Li, Y.; Oyen, M. L.; Stuart, M. A. C.; Boehm, H.; Li, B.; Vogel, V.; Spatz, J. P.; Watt, F. M.; et al. (Nat. Mater., 2012)

(untitled) - Dalby, M. J.; Andar, A.; Nag, A.; Affrossman, S.; Tare, R.; McFarlane, S.; Oreffo, R. O. C. (J. R. Soc., Interface, 2008)

(untitled) - McMurray, R. J.; Gadegaard, N.; Tsimbouri, P. M.; Burgess, K. V.; McNamara, L. E.; Tare, R.; Murawski, K.; Kingham, E.; Oreffo, R. O. C.; Dalby, M. J. (Nat. Mater., 2011)

(untitled) - Guarda, A.; Bolognese, F.; Bonapace, I. M.; Badaracco, G. (Exp. Cell Res., 2009)

(untitled) - Swift, J.; Ivanovska, I. L.; Buxboim, A.; Harada, T.; Dingal, P. C. D. P.; Pinter, J.; Pajerowski, J. D.; Spinler, K. R.; Shin, J.-W.; Tewari, M.; Rehfeldt, F.; Speicher, D. W.; et al. (Science, 2013)

(untitled) - Lind, M. (Acta Orthop. Scand., 1996)

(untitled) - Nimni, M. E. (Biomaterials, 1997)

(untitled) - Rose, F. R. A. J.; Hou, Q.; Oreffo, R. O. C. (J. Pharm. Pharmacol., 2004)

(untitled) - Masters, K. S. (Macromol. Biosci., 2011)

(untitled) - Rengachary, S. S. (Neurosurg. Focus, 2002)

(untitled) - Barrientos, S.; Stojadinovic, O.; Golinko, M. S.; Brem, H.; Tomic-Canic, M. (Wound Repair Regen., 2008)

(untitled) - Bianco, P.; Robey, P. G. (Nature, 2001)

(untitled) - Schulz, T. J.; Tseng, Y.-H. (Cytokine Growth Factor Rev., 2009)

(untitled) - Helm, G.; Anderson, D. G.; Andersson, G. B. J.; Boden, S. D.; Damien, C.; Ebara, S.; Lane, J. M.; McKay, B.; Sandhu, H. S.; Seeherman, H.; Wozney, J. (Spine, 2002)

(untitled) - Hogan, B. L. (Genes Dev., 1996)

(untitled) - Bessa, P. C.; Casal, M.; Reis, R. L. (J. Tissue Eng. Regener. Med., 2008)

(untitled) - Shimasaki, S.; Moore, R. K.; Otsuka, F.; Erickson, G. F. (Endocr. Rev., 2004)

(untitled) - Schlunegger, M. P.; Grütter, M. G. (Nature, 1992)

(untitled) - Scheufler, C.; Sebald, W.; Hülsmeyer, M. (J. Mol. Biol., 1999)

(untitled) - Nohe, A.; Hassel, S.; Ehrlich, M.; Neubauer, F.; Sebald, W.; Henis, Y. I.; Knaus, P. (J. Biol. Chem., 2002)

(untitled) - Wozney, J. M.; Rosen, V. (Clin. Orthop. Relat. Res., 1998)

(untitled) - Rosen, V. (Ann. N. Y. Acad. Sci., 2006)

(untitled) - Chen, D.; Zhao, M.; Harris, S. E.; Mi, Z. (Front. Biosci., 2004)

(untitled) - Tendijke, P.; Yamashita, H.; Sampath, T. K.; Reddi, A. H.; Estevez, M.; Riddle, D. L.; Ichijo, H.; Heldin, C. H.; Miyazono, K. (J. Biol. Chem., 1994)

(untitled) - Koenig, B. B.; Cook, J. S.; Wolsing, D. H.; Ting, J.; Tiesman, J. P.; Correa, P. E.; Olson, C. A.; Pecquet, A. L.; Ventura, F. S.; Grant, R. A.; Chen, G.-X.; Wrana, J. L.; et al. (Mol. Cell. Biol., 1994)

(untitled) - Kirsch, T.; Sebald, W.; Dreyer, M. K. (Nat. Struct. Biol., 2000)

(untitled) - Kirsch, T.; Nickel, J.; Sebald, W. (EMBO J., 2000)

(untitled) - Keller, S.; Nickel, J.; Zhang, J.-L.; Sebald, W.; Mueller, T. D. (Nat. Struct. Mol. Biol., 2004)

(untitled) - Sebald, W.; Nickel, J.; Zhang, J.-L.; Mueller, T. D. (Biol. Chem., 2004)

(untitled) - Miyazono, K.; Maeda, S.; Imamura, T. (Cytokine Growth Factor Rev., 2005)

(untitled) - Xiao, Y.-T.; Xiang, L.-X.; Shao, J.-Z. (Biochem. Biophys. Res. Commun., 2007)

(untitled) - Sieber, C.; Kopf, J.; Hiepen, C.; Knaus, P. (Cytokine Growth Factor Rev., 2009)

(untitled) - Bishop, G. B.; Einhorn, T. A. (Int. Orthop., 2007)

(untitled) - Gittens, S. A.; Uludag, H. (J. Drug Targeting, 2001)

(untitled) - Burg, K. J. L.; Porter, S.; Kellam, J. F. (Biomaterials, 2000)

(untitled) - V, L.; Meinel, L.; Merkle, H. P.; Gander, B. (Eur. J. Pharm. Biopharm., 2004)

(untitled) - Vasita, R.; Katti, D. S. (Expert Rev. Med. Devices, 2006)

(untitled) - McKay, B.; Sandhu, H. S. (Spine, 2002)

(untitled) - Reddi, A. H. (J. Cell. Biochem., 1994)

(untitled) - Solheim, E. (Int. Orthop., 1998)

(untitled) - Mehta, M.; Schmidt-Bleek, K.; Duda, G. N.; Mooney, D. J. (Adv. Drug Delivery Rev., 2012)

(untitled) - Pohl, T. L. M.; Boergermann, J. H.; Schwaerzer, G. K.; Knaus, P.; Cavalcanti-Adam, E. A. (Acta Biomater., 2012)

(untitled) - Schwab, E. H.; Pohl, T. L. M.; Haraszti, T.; Schwaerzer, G. K.; Hiepen, C.; Spatz, J. P.; Knaus, P.; Cavalcanti-Adam, E. A. (Nano Lett., 2015)

(untitled) - Chen, G.; Gulbranson, D. R.; Yu, P.; Hou, Z.; Thomson, J. A. (Stem Cells, 2012)

(untitled) - Crouzier, T.; Fourel, L.; Boudou, T.; Albigès-Rizo, C.; Picart, C. (Adv. Mater., 2011)

(untitled) - Park, J. S.; Yang, H. N.; Jeon, S. Y.; Woo, D. G.; Na, K.; Park, K.-H. (Biomaterials, 2010)

(untitled) - Shekaran, A.; Garcia, J. R.; Clark, A. Y.; Kavanaugh, T. E.; Lin, A. S.; Guldberg, R. E.; Garcia, A. J. (Biomaterials, 2014)

(untitled) - Ivaska, J.; Heino, J. (Annu. Rev. Cell Dev. Biol., 2011)

(untitled) - Schwartz, M. A.; Ginsberg, M. H. (Nat. Cell Biol., 2002)

(untitled) - Yamada, K. M.; Even-Ram, S. (Nat. Cell Biol., 2002)

(untitled) - Danen, E. H. J.; Yamada, K. M. (J. Cell. Physiol., 2001)

(untitled) - Schwartz, M. A.; Assoian, R. K. (J. Cell Sci., 2001)

(untitled) - Moro, L.; Venturino, M.; Bozzo, C.; Silengo, L.; Altruda, F.; Beguinot, L.; Tarone, G.; Defilippi, P. (EMBO J., 1998)